Impact of Leadership Style on Staff Retention: Exploring the Impact of Leadership Style on Staff Retention in the Indian Banking Sector (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The study explores the grandeur of leadership and offers a concise account of how types of management influence the success of staff in a company. The paper further explains the value and value of maintaining important human capital through suitable management principles and types. The retention of staff is deemed one of the key problems in the present business environment. To fuel productivity, company enterprises must implement strategies to attract successful employees and take the appropriate measures to maintain them. The study aimed to define the leadership types impacting the retention of workers in the Indian banking sector. The researchers obtained first-hand knowledge from the bank workers through a well-structured questionnaire. The researcher absorbed the random sampling procedure and 100 employees of the private sector banks from the area of Chennai were taken for the analysis. With a multivariate statistical methodology named factor analyses, one-way study of the variance and the multiple regression, aside from general descriptive statistics, the opinion of employees about management variables on employee performance was analyzed. Therefore, the empirical approach is used for data analysis and understanding. In basic terms, an entity will be affected adversely from bank operations to the strategic level if best employees are not kept inside the group.